Recent Advancement in Fluorescent Probes for Peroxynitrite (ONOO−) - Han, Hai-Hao; Ge, Pan-Xin; Li, Wen-Jia; Hu, Xi-Le; He, Xiao-Peng (Sensors (Basel, Switzerland), 2025)
Peroxynitrite (ONOO−) is a reactive nitrogen species (RNS) that plays pivotal roles in various physiological and pathological processes. The recent literature has seen significant progress in the development of highly sensitive and selective fluorescent probes applicable for monitoring ONOO− dynamics in live cells and a variety of animal models of human diseases. However, the clinical applications of those probes remain much less explored. This review delves into the biological roles of ONOO− and summarizes the design strategies, sensing mechanisms, and bioimaging applications of near-infrared (NIR), long-wavelength, two-photon, and ratiometric fluorescent probes modified with a diverse range of functional groups responsive to ONOO−. Furthermore, we will discuss the remaining problems that prevent the currently developed ONOO− probes from translating into clinical practice.